A TEACHING MATERIAL FOR LEARNING ALTERNATING CURRENT CIRCUIT USING SOUNDCARD OSCILLOSCOPE -EXPERIMENTS FOR THE ELECTRICAL RESONANCE- - Hasanah, Uswatun; Massango, Herieta; Tsutaoka, Takanori (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
Nowadays, the lack of a facility is one of the main problems in physics education for developing countries. To solve the problem by use of the modern technology which develop around the world obviously, a teaching material in learning alternating current (AC) circuit as one of the most difficult theory in physics for secondary school students has been investigated using a soundcard oscilloscope with the laptop computer. Experiments for the electrical resonance in LCR circuits have been investigated using the sound card oscilloscope; experimental results were compared to that measured by the conventional oscilloscope system. As expected, the investigated soundcard oscilloscope experiments show a good performance; the magnitude of electrical current as a frequency response proves the effectiveness of the teaching material in physics education that shows kind of limited function of soundcard oscilloscope that utilizes as a benefit in a simple experiment. For the further work, the teacher can utilize and develop this software for the other teaching materials for example related to traditional music or traditional apparatus which tend to find around student’ home or school, so students can understand more deeply about the concept of alternating current in many cases and more interesting classes can be created.